2024
DOI: 10.1038/s41598-024-52549-8
|View full text |Cite|
|
Sign up to set email alerts
|

A multinational study on the factors influencing university students’ attitudes and usage of ChatGPT

Maram Abdaljaleel,
Muna Barakat,
Mariam Alsanafi
et al.

Abstract: Artificial intelligence models, like ChatGPT, have the potential to revolutionize higher education when implemented properly. This study aimed to investigate the factors influencing university students’ attitudes and usage of ChatGPT in Arab countries. The survey instrument “TAME-ChatGPT” was administered to 2240 participants from Iraq, Kuwait, Egypt, Lebanon, and Jordan. Of those, 46.8% heard of ChatGPT, and 52.6% used it before the study. The results indicated that a positive attitude and usage of ChatGPT we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 96 publications
0
18
0
1
Order By: Relevance
“…Recent research found the negative effect of perceived risk on acceptance of generative AI, which showed that when students and faculty member believed that using generative AI for answering academic queries is risky, they did not think that generative AI in higher education is good for society (Jain & Raghuram, 2024). A multinational study replicated this result (Abdaljaleel et al, 2024). If perceived risk has a negative effect on accepting new technologies, as universities perceives potential risks associated with the use of generative AI tools in higher education, they should be cautious about endorsing its acceptance.…”
Section: Hypothesismentioning
confidence: 90%
See 2 more Smart Citations
“…Recent research found the negative effect of perceived risk on acceptance of generative AI, which showed that when students and faculty member believed that using generative AI for answering academic queries is risky, they did not think that generative AI in higher education is good for society (Jain & Raghuram, 2024). A multinational study replicated this result (Abdaljaleel et al, 2024). If perceived risk has a negative effect on accepting new technologies, as universities perceives potential risks associated with the use of generative AI tools in higher education, they should be cautious about endorsing its acceptance.…”
Section: Hypothesismentioning
confidence: 90%
“…Facilitating conditions are positively associated with acceptance of generative AI Perceived risk refers to an individual's subjective evaluation of the potential negative outcomes associated with a speci c action (Abdaljaleel et al, 2024;Ben Ar et al, 2021;Zhang et al, 2019). In the context of generative AI in higher education policies, such risk covers the degree to which a university perceives potential risks associated with the use of generative AI tools in academics such as cheating, misinformation use, and copyright violation, which undermine student learning.…”
Section: Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…Using this survey, we found evidence of changing views and knowledge about ChatGPT and AI since spring 2023. However, we acknowledge our data and survey methodology are limited, and other researchers may wish to use formally validated instruments (e.g., “TAME-ChatGPT”). Regardless of methodology, we believe it is important for chemistry instructors to continue assessing students’ views and knowledge of AI tools to ensure they are well prepared for future work in our discipline.…”
Section: Conclusion and Implications For Instruction And Researchmentioning
confidence: 99%
“…Uno de los últimos avances basados en la IA es ChatGPT, (7) un modelo de lenguaje grande (LLM, por sus siglas en inglés) desarrollado por OpenAI, que surgió como una innovación que cambió el paradigma para la adquisición de información. (8) Esta herramienta posee la capacidad de comprender y generar lenguaje humano de forma coherente y contextual, lo que la posiciona como una potente herramienta de procesamiento de lenguaje natural.…”
Section: Introductionunclassified